Numerical investigation on the effect of bileaflet mechanical heart valve's implantation tilting angle and aortic root geometry on intermittent regurgitation and platelet activation. Issue 2 (4th August 2019) - Abbas, Syed Samar; Nasif, Mohammad Shakir; Al‐Waked, Rafat; Meor Said, Mior Azman
Abstract: Platelet activation induced by shear stresses and non‐physiological flow field generated by bileaflet mechanical heart valves (BMHVs) leads to thromboembolism, which can cause fatal consequences. One of the causes of platelet activation could be intermittent regurgitation, which arises due to asynchronous movement and rebound of BMHV leaflets during the valve closing phase. In this numerical study, the effect of intermittent regurgitation on the platelet activation potential of BMHVs was quantified by modeling a BMHV in the straight and anatomic aorta at implantation tilt angles 0°, 5°, 10°, and 20°. A fully implicit Arbitrary Lagrangian–Eulerian‐based Fluid–Structure Interaction formulation was adopted with blood modeled as a multiphase, non‐Newtonian fluid. Results showed that the intermittent regurgitation and consequently the platelet activation level increases with the increasing implantation tilt of BMHV. For the straight aorta, the leaflet of the 20° tilted BMHV underwent a rebound of approximately 20° after initially closing, whereas the leaflet of the 10°, 5°, and 0° tilted BMHVs underwent a rebound of 8.5°, 3°, and 0°, respectively. For the anatomic aorta, the leaflet of the 20° tilted BMHV underwent a rebound of approximately 24° after initially closing, whereas the leaflet of the 10°, 5°, and 0° tilted BMHVs underwent a rebound of 14°, 10°, and 7°, respectively. For all the implantation orientations of BMHVs, intermittent regurgitation and platelet activation were always higher in the anatomic aorta than in the straight aorta. The study concludes that the pivot axis of BMHV must be implanted parallel to the aortic root's curvature to minimize intermittent regurgitation and platelet activation.